Quantitative Analysis of 18 Marker Components in the Traditional Korean Medicine, Cheongsangbangpung-Tang, Using High-Performance Liquid Chromatography Combined with Photodiode Array Detector - Chang-Seob Seo; Hyeun-Kyoo Shin (Applied Sciences, 2020)
Cheongsangbangpung-tang (CSBPT) is a traditional herbal medicine that has been used in many regions of Asia, including Korea, China, and Japan, for the treatment of purulent inflammation and eczema on the face. In this study, a method for the simultaneous analysis of 18 marker components, geniposide (1), coptisine chloride (2), prim-O-glucosylcimifugin (3), berberine chloride (4), liquiritin apioside (5), liquiritin (6), ferulic acid (7), narirutin (8), 5-O-methylvisammisoide (9), hesperidin (10), arctigenin (11), baicalin (12), oxypeucedanin hydrate (13), wogonoside (14), baicalein (15), arctiin (16), glycyrrhizin (17), and pulegone (18), was developed for quality control of CSBPT. The novel approach, which is based on high-performance liquid chromatography (HPLC) separation coupled with photodiode array detection, was verified by the assessment of linearity, limit of detection, limit of quantification, accuracy, recovery, and precision. Analysis of CSBPT by using the established assay revealed that compounds 1–18 were present in concentrations of 0.27–18.31 mg/g.